Reflexively-Contextual Educational Environment as a Factor of Professional Preparation of the Future Primary School Teacher in Higher Educational Institution - Viktoria Zhelanova (Pedagogical Discourse, 2012)
The definition analysis of the concepts „environment”, „educational environment”, „reflection-educational environment”, „contextual environment” is carried out in the presented article, and the author’s understanding of these phenomena is grounded. The  concept „reflexively-contextual educational environment” is introduced and described, its features, structure  in accordance with conception of the context teaching are revealed.